Urban development zones (UDZS): an investigation of the perceptions of stake holders on the impacts of the UDZ tax incentive on property development in Johannesburg inner city - Sibutu, Mwangala Elham (My University, 2012)
South Africa, like most countries world over, has undergone and continues to suffer from urban decay in varying stages. The inner city of Johannesburg is considered as one of the most decayed cities in South Africa. To this end, urban regeneration strategies based primarily on international models have been introduced and implemented in South Africa. The Urban Development Zone (UDZ) tax incentive is one such strategy. It was introduced as a post apartheid strategy to regenerate the inner cities of 16 municipalities, Johannesburg being one of them, by enhancing private investment. This study sought to investigate the perceptions of the stakeholders on the impacts of the UDZ tax incentive on property development in Johannesburg inner city. Data was collected from a purposively selected group of policy makers (officials from Johannesburg Development Agency, JDA, Johannesburg Property Company, JPC and Johannesburg Metropolitan Municipality) and property developers active in Johannesburg inner city. The findings of the research indicated that property developers were profit driven and the demand for built up space in the inner city and potential for rental growth have been the major driving force of property development. Since the study sought to explore the views, opinions, perceptions and attitudes of the stake holders, the survey research strategy was considered the most appropriate method to collect and analyse primary and secondary data. The main finding of the survey was that, the stake holders did not consider the UDZ tax incentive as an adequately motivating factor to encourage property development in the inner city.